Propensity score-matched analysis of oncological outcome between stent as bridge to surgery and emergency resection in patients with malignant left-sided colonic obstruction. Issue 8 (10th May 2019) - Amelung, F J; Borstlap, W A A; Consten, E C J; Veld, J V; van Halsema, E E; Bemelman, W A; Siersema, P D; ter Borg, F; van Hooft, J E; Tanis, P J; Algera, H; Algie, G D; et al.
Abstract: Background: Although self-expandable metal stent (SEMS) placement as bridge to surgery (BTS) in patients with left-sided obstructing colonic cancer has shown promising short-term results, it is used infrequently owing to uncertainty about its oncological safety. This population study compared long-term oncological outcomes between emergency resection and SEMS placement as BTS. Methods: Through a national collaborative research project, long-term outcome data were collected for all patients who underwent resection for left-sided obstructing colonic cancer between 2009 and 2016 in 75 Dutch hospitals. Patients were identified from the Dutch Colorectal Audit database. SEMS as BTS was compared with emergency resection in the curative setting after 1 : 2 propensity score matching. Results: Some 222 patients who had a stent placed were matched to 444 who underwent emergency resection. The overall SEMS-related perforation rate was 7·7 per cent (17 of 222). Three-year locoregional recurrence rates after SEMS insertion and emergency resection were 11·4 and 13·6 per cent ( P = 0·457), disease-free survival rates were 58·8 and 52·6 per cent ( P = 0·175), and overall survival rates were 74·0 and 68·3 per cent ( P = 0·231), respectively. SEMS placement resulted in significantly fewer permanent stomas (23·9 versus 45·3 per cent; P < 0·001), especially in elderly patients (29·0 versus 57·9 per cent; P < 0·001). For patients in the SEMS group with or without perforation, 3-year locoregional recurrence rates were 18 and 11·0 per cent ( P = 0·432), disease-free survival rates were 49 and 59·6 per cent ( P = 0·717), and overall survival rates 61 and 75·1 per cent ( P = 0·529), respectively. Conclusion: Overall, SEMS as BTS seems an oncologically safe alternative to emergency resection with fewer permanent stomas. Nevertheless, the risk of SEMS-related perforation, as well as permanent stoma, might influence shared decision-making for individual patients. Graphical Abstract: The disease-free and overall survival of patients with left-sided obstructive colonic cancer treated with either emergency resection or stent placement and elective resection was compared using a propensity score-matched analysis. No difference was found in any of the oncological outcome measures. Patients treated with stent placement, however, had significantly fewer permanent stomas. Self-expandable metal stent oncologically safe